Projected Economic Impact of Climate Change on Marine Capture Fisheries in the Philippines - Suh, David; Pomeroy, Robert (Frontiers in Marine Science, 2020)
Climate change and its impact on fisheries is a key issue for fishing nations, particularly the Philippines. The Philippine is highly vulnerable to the impacts of climate change on fisheries and it can lead to economic shock on the nation’s economy. This paper examines the impact of climate change on marine capture fisheries in the Philippines using an economic model to elaborate and project impacts on the national economy. In the simulation, one baseline scenario and two climate change scenarios based on greenhouse gas concentration were considered. The model focuses on Gross Domestic Product (GDP) and income distribution by region, which can represent economic conditions in terms of economic growth and distribution. Results show that there will be a negative change on both the fisheries and economic variables where more extreme changes in climate occur.